Gender related Long-term Differences after Open Infrainguinal Surgery for Critical Limb Ischemia. Issue 4 (October 2015) - Lejay, A.; Schaeffer, M.; Georg, Y.; Lucereau, B.; Roussin, M.; Girsowicz, E.; Delay, C.; Schwein, A.; Thaveau, F.; Geny, B.; Chakfe, N.
Abstract : Objective: The role of gender on long-term infrainguinal open surgery outcomes still remains uncertain in critical limb ischemia patients. The aim of this study is to evaluate the gender-specific differences in patient characteristics and long-term clinical outcomes in terms of survival, primary patency and limb salvage among patients undergoing infrainguinal open surgery for CLI. Material and methods: All consecutive patients undergoing infrainguinal open surgery for critical limb ischemia between 2003 and 2012 were included. Survival, limb salvage and primary patency rates were assessed. Independent outcome determinants were identified by the Cox proportional hazard ratio using age and gender as adjustment factors. Results: 584 patients (269 women and 315 men, mean age 76 and 71 years respectively) underwent 658 infrainguinal open surgery (313 in women and 345 in men). Survival rate at 6 years was lower among women compared to men with 53.5% vs 70.9% ( p < 0.001 ). The same applied to primary patency (35.9% vs 52.4%, p < 0.001 ) and limb salvage (54.3% vs 81.1%, p < 0.001 ) at 6 years. Female-gender was an independent factor predicting death (hazard ratio 1.50), thrombosis (hazard ratio 2.37) and limb loss (hazard ratio 7.05) in age and gender-adjusted analysis. Conclusion: Gender-related disparity in critical limb ischemia open surgical revascularization outcomes still remains.